Healthy Hospital Food Environment: the PCMH Story. - Kolasa, Kathryn M.; Gaskins, Scottie; Dial, Jeff; Ho, Amanda; Currie, Russ; Comeaux, Preston; Robertson, Roger (My University, 2006)
This paper describes Pitt Memorial Hospital's response to the call to become a healthy worksite. It describes the hospital's effots to partner in the North Carolina Plan to Prevent Overweight and Obesity and Related Chronic Conditions. Way to define healthy eating, healthy snacks, healthy vending, healthy cafeteria are described.
Perspectives in Practice is a journal published by the Pitt Memorial Hospital to distribute scholarly work of its employees.
Keywords: Healthy hospital; Food environment; Obesity prevention